Implementation of Contextual Discovery Learning Model to Improve Scientific Literacy - Ullum, Iva Tien Nur Hidayatul; Martini, Martini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Scientific literacy is an essential 21st-century competency that enables students to explain scientific phenomena, design investigations, and interpret evidence-based data. This study aims to analyze the improvement of students' scientific literacy through the application of the Discovery Learning model with a contextual approach to human respiration material. The learning context is developed through a comparative analysis of air pollution data from urban and rural areas, enabling students to examine the relationship between air quality and respiratory system disorders in a real and relevant manner. This study used a quantitative method with a one-group pretest-posttest design. The subjects were 31 eighth-grade students of SMP Negeri 1 Selorejo. The instruments used included a scientific literacy test (pretest and posttest), an observation sheet for learning implementation, and a student response questionnaire. Data analysis was carried out in stages, beginning with a normality test to determine data distribution. Because the data were not normally distributed, hypothesis testing was continued using the non-parametric Wilcoxon test. The magnitude of the increase was calculated through the N-Gain value. The results showed a significant increase in scientific literacy, as indicated by the Wilcoxon test, with an N-Gain of 0.70, which falls within the moderate category. These findings demonstrate that integrating Discovery Learning with a contextual approach grounded in urban and rural air pollution data effectively facilitates students' connections between respiratory system concepts and real-world environmental issues. Thus, this learning model contributes to strengthening scientific literacy competencies in a more meaningful and contextual way.